(untitled) - Maginn, Michael D. (New York, NY., 2005)
While change is essential to your organization's survival, it can also breed instability, stress, and even anger among your workforce. Managing in Times of Change shows you how to help managers and employees understand the benefits of change, then flourish within their new environment and responsibilities. Two dozen workplace-proven leadership lessons and tools provide you with a uniquely personal look at the impact of organizational change, detailing strategies to: Communicate and personify the benefits of change * Isolate and clarify areas of impact * Paint a consistent picture of what is happening * Measure and celebrate progress * Get team members involved * Empathize without always agreeing
Keywords: Industrial management.,Organizational change